2019
DOI: 10.1371/journal.pone.0225659
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the solubility of yeast cell wall preparations on their potential prebiotic properties in dogs

Abstract: Derivatives of yeast cell wall (YCW) have been studied for their potential prebiotic effects. Recently, new purified and soluble preparations have been developed in an attempt to increase their biological actions. Two YCW preparations, one conventional and another with higher solubility of the mannan oligosaccharide fraction, were evaluated on dogs. One food formulation was used, divided into the following treatments: CON–control, without yeast cell wall addition; YCW–addition of 0.3% of a conventional yeas ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 82 publications
(104 reference statements)
1
23
1
9
Order By: Relevance
“…However, other studies that have used higher levels of prebiotics (from 1 to 3 g/day and 15 g/kg of diet) showed an increase in SCFA concentrations [23,28,32] and the higher concentration of the prebiotic may have an impact on a different result. The unchanged concentration of BCFA was expected, since most studies have found no effect for this variable [11][12][13]18,19,21,26,27,29,33,64].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, other studies that have used higher levels of prebiotics (from 1 to 3 g/day and 15 g/kg of diet) showed an increase in SCFA concentrations [23,28,32] and the higher concentration of the prebiotic may have an impact on a different result. The unchanged concentration of BCFA was expected, since most studies have found no effect for this variable [11][12][13]18,19,21,26,27,29,33,64].…”
Section: Discussionmentioning
confidence: 86%
“…Most studies (39% of 23 studies) with prebiotic interventions used a shorter period, on average 14 days [7,[10][11][12][13][14][18][19][20] with few benefits that would justify its inclusion. On the other hand, 26% of the studies evaluated different prebiotics for an average of 24 days [21][22][23][24][25][26] and 13% evaluated for 33 days on average [27][28][29]. About 13% evaluated the long-term effects during 220 days on average [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, higher fecal IgA after a prebiotic supplementation may be interpreted as an enhancement effect of beneficial bacteria and their products on the intestinal immune system [ 58 ]. Accordingly, previous studies investigating prebiotics [ 59 ] and probiotics [ 60 ] in dogs showed an improvement of intestinal IgA excretion, although the literature offers conflicting results in this regard [ 61 , 62 , 63 ]. In the present study, an increase in fecal IgA would have been explained as an expression of immune stimulatory activity exerted by seaweed supplementation, similar to previous studies in other animal species, albeit other immunological parameters such as tumor necrosis factor or interleukins have been investigated more often in this context [ 18 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher butyrate may result in better nutrient and energy supply to colonocytes, allowing better development of the intestinal mucosal barrier and histological structure (Peixoto et al, 2018; Topping & Clifton, 2001). Butyrate may also reduce inflammation and increase local and systemic immunity in animals (Ashwar et al, 2016; Bird et al, 2007; Birt et al, 2013; Maria et al, 2017; Theodoro et al, 2019; Zaman & Sarbini, 2015), aspects that can also be explored in cats. So, considering the effects on butyrate levels, in terms of potential implications for gut health, moderate starch gelatinization reducing the energy application to mass might be interesting and further investigated to better substantiate the processing parameters defined for pet foods.…”
Section: Discussionmentioning
confidence: 99%